Purtscher's retinopathy. - Buckley, S. A. (BMJ Group, 1996)
Purtscher's retinopathy presents to the clinician as loss of vision in a patient with a history of a possible precipitating event such as recent major trauma, pancreatitis, childbirth or renal failure. The ophthalmological picture is one of ischaemia at the posterior pole with white patches of oedema and haemorrhages concentrated around the optic disc. The most probable pathological cause is embolisation of the peripapillary terminal arterioles supplying the superficial peripapillary capillary net. The nature of the embolic particles remains uncertain. Complement-mediated aggregates, fat, air, fibrin clots and platelet clumps may all be involved in what is most likely to be a multifactorial process. There is at present no recognised treatment for the condition.